2017
DOI: 10.7150/ijbs.18430
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate fraction of Huogu formula inhibits adipogenic differentiation of bone marrow stromal cells via the BMP and Wnt signaling pathways

Abstract: Elevated adipogenesis of bone marrow stromal cells (BMSCs) is closely associated with non-traumatic osteonecrosis of femoral head (ONFH). Our previous studies have shown that Huogu (HG) formula was effective both in clinic experience and experimental ONFH. How HG impacts the differentiation of BMSCs and what is the underlying molecular mechanism remain largely unknown. Our results showed that ethyl acetate extract of HG (HGE) significantly decreased the adipocyte differentiation as determined by oil red staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…During myocardial I/R injury, ROS production from the mitochondria and Nox is implicated in oxidative stress injury in cardiomyocytes (22). Nox is an enzyme also expressed in phagocytes; however, Nox in myocardial cells differs in its catalytic characteristics and biological functions: Cardiac muscle Nox is weakly active under physiological conditions, whereas ROS production is a critical function of phagocytosis; cardiac Nox and NADPH or nicotinamide adenine dinucleotide (NADH) are electron donors, whereas only NADPH is an electron donor in phagocytes; in phagocytes, Nox-generated ROS mainly participate in the host mechanisms of defense (23,24), whereas in cardiomyocytes ROS function as a second messenger during the regulation of cellular proliferation and differentiation (22). The results of the present study revealed that anisodamine significantly reversed the I/R-induced decrease in SOD levels and increase in MDA levels in serum samples isolated from rats following I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During myocardial I/R injury, ROS production from the mitochondria and Nox is implicated in oxidative stress injury in cardiomyocytes (22). Nox is an enzyme also expressed in phagocytes; however, Nox in myocardial cells differs in its catalytic characteristics and biological functions: Cardiac muscle Nox is weakly active under physiological conditions, whereas ROS production is a critical function of phagocytosis; cardiac Nox and NADPH or nicotinamide adenine dinucleotide (NADH) are electron donors, whereas only NADPH is an electron donor in phagocytes; in phagocytes, Nox-generated ROS mainly participate in the host mechanisms of defense (23,24), whereas in cardiomyocytes ROS function as a second messenger during the regulation of cellular proliferation and differentiation (22). The results of the present study revealed that anisodamine significantly reversed the I/R-induced decrease in SOD levels and increase in MDA levels in serum samples isolated from rats following I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in their activation mechanisms, Nox2 needs to be induced in order to generate O 2-, whereas Nox4 can constitutively generate low levels of H 2 O 2 (26). Furthermore, Nox4 in cardiac muscle cells can catalyze O 2generation effectively, using NADH as a hydrogen donor (23). Due to the autonomous activity of Nox4, NADH is highly used in cardiac muscle cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of both canonical and noncanonical Wnt signalling in the osteogenesis of stem cells has been widely explored in many studies in vivo and in vitro [12,13]. Wnt5a signalling suppresses adipogenesis by suppressing the transcriptional activity of PPAR-γ and promotes the differentiation of BMSCs into osteoblasts [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that ischemia, caused by interruption of the blood supply to the femoral head, is a primary cause of ONFH . In addition to osteocyte apoptosis, bone resorption, and adipocyte accumulation are also components of the progression of this disease …”
Section: Patient Demographics and Harris Hip Score (Hhs)mentioning
confidence: 99%